TRADISI AMALAN EMPAT SURAH DI PONPES DAARUL ULUM PUTRI, PEKANBARU RIAU : Studi Living Qur’an - Aulia, Sarah; Rahman, Yenni; Wardani, Febri (LPPM STAI Muhammadiyah Probolinggo, 2025)
This research is based on the practice of living Qur'an or Al-Qur'an in everyday life Abstract This research departs from the practice of practicing the Qur'an in daily life at the Daarul Ulum Putri Pekanbaru Islamic Boarding School, especially in the implementation of the practice of four surahs (Yasin, Al-Mulk, As-Sajdah, and Ad-Dukhan) which is carried out every Friday night. This research aims to understand the meaning and procedures for implementing these practices. The type of research used is field research with a qualitative descriptive approach within the framework of Living Qur'an. Data collection techniques involve observation, interviews, and documentation. The results of the study show that the practice of these four surahs is a habit that has become a tradition at the Daarul Ulum Putri Islamic Boarding School, Pekanbaru, which is carried out every Friday night. This activity aims to increase understanding and appreciation of the content of the Qur'an. The students follow this practice with the guidance of the hut caretakers, who explain the virtues and wisdom behind the recitation of the surahs. With this tradition, it is hoped that the students can apply the values of the Qur'an in their daily lives.